Los cuentos cortos como estrategia didáctica para la optimización de la competencia lingüística - Espinoza Gavilanez, Jeremy Ruben (2024)
In the research work, an investigation was carried out about "Stories as a didactic strategy for the optimization of linguistic competence" to analyze the stories as a didactic strategy for the optimization of linguistic competence in the Unidad Educativa "Huambi" in the tenth grade of E.G.B., for which similar works were sought to have a background about the job done, which allowed to improve the research process. Then, each variable was broken down to perform deductive research, starting from the general to the particular, allowing the work to be supported best. The research methodology was quantitative since it allowed data to be collected and interpreted numerically and according to the questions asked. It is worth mentioning that for data collection, the questionnaire was used as a technique and the survey as an instrument since it was applied to the students of the aforementioned educational unit. After interpreting the data, it was concluded that stories are a fundamental tool to enhance linguistic competence since they improve all the skills immersed in the competencies.